2007
DOI: 10.1007/s11661-007-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Characterization of the Bake-Hardening Behavior of Transformation-Induced Plasticity and Dual-Phase Steels

Abstract: The effect of prestraining (PS) and bake hardening (BH) on the microstructures and mechanical properties has been studied in transformation-induced plasticity (TRIP) and dual-phase (DP) steels after intercritical annealing. The DP steel showed an increase in the yield strength and the appearance of the upper and lower yield points after a single BH treatment as compared with the as-received condition, whereas the mechanical properties of the TRIP steel remained unchanged. This difference appears to be because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 21 publications
3
60
0
1
Order By: Relevance
“…[33] A decrease in work hardening rate with an increase in the dislocation density in ferrite was observed previously in bake-hardened TRIP and DP steels. [34] The discontinuous yielding behavior observed here for the samples deformed at 1098 K (825°C) could be related to the formation of Cottrell atmospheres. However, the carbon content in solid solution was similar for all the studied TMP conditions (see the calculations below).…”
Section: B Effect Of Tmp On Mechanical Propertiesmentioning
confidence: 62%
“…[33] A decrease in work hardening rate with an increase in the dislocation density in ferrite was observed previously in bake-hardened TRIP and DP steels. [34] The discontinuous yielding behavior observed here for the samples deformed at 1098 K (825°C) could be related to the formation of Cottrell atmospheres. However, the carbon content in solid solution was similar for all the studied TMP conditions (see the calculations below).…”
Section: B Effect Of Tmp On Mechanical Propertiesmentioning
confidence: 62%
“…The presence of a local minimum on the strain-hardening rate curve (Figure 12 inset) proves that the dislocation unlocking process is responsible for the observed yield point drop in this steel, contrary to the mechanism of the formation of new dislocations in the TRIP steels with a high volume fraction of polygonal ferrite. [17,34] IV. CONCLUSIONS Application of APT to study nanobainitic steels allowed us to elucidate the alloying element redistribution between phases and gain insight into the mechanism of phase transformations.…”
Section: Micro-and Nanoscale Analysismentioning
confidence: 99%
“…[30][31][32][33][34] This is an important contribution to in-service properties, such as a low springback and improved dent and crash resistance. [32] Extensive investigations have established the mechanisms and stages of the bake hardening behavior of low carbon steels, which are controlled by the amount of interstitial carbon atoms and the formation of Cottrell atmosphere and precipitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of the TRIP steels consists of polygonal ferrite, carbide-free bainite morphologies, retained austenite and martensite. As previous studies using electron microscopy have shown [9][10][11][12][13], during pre-straining and bake hardening various microstructural changes take place: increase in dislocation density, especially in polygonal ferrite in the vicinity of hard martensite or retained austenite crystals, strain-induced transformation of austenite to martensite and precipitation of fine carbides in the bainitic ferrite.…”
Section: Introductionmentioning
confidence: 99%